Pre-existing arterial pathologic changes affecting arteriovenous fistula patency and cardiovascular mortality in hemodialysis patients - Lee, Ja Young (Korean J Intern Med, 2017)
The radiocephalic arteriovenous fistula (AVF) provides optimal vascular access for hemodialysis; it has a higher long-term patency rate and fewer complications than other vascular access methods. However, the AVF has a high primary failure rate. The presence of small-diameter vessels at anastomosis sites is an important risk factor for AVF failure. However, in a recent study, despite selecting an adequate artery and vein for creating an AVF by routine preoperative vascular mapping, AVF maturation and primary failure occurred. Thus, pre-existing arteriosclerosis at AVF anastomosis sites likely contributes to AVF failure. In this review, we discuss the relationship between pathologic changes and AVF patency in hemodialysis patients. Because arteriosclerosis of the major arteries such as the coronary and carotid arteries is associated with cardiovascular mortality, we also review the impact of arteriosclerosis of upper arm arteries at AVF anastomosis sites on cardiovascular mortality in hemodialysis patients.